2003
DOI: 10.1021/cm031114n
|View full text |Cite
|
Sign up to set email alerts
|

Polycrystalline Well-Shaped Blocks of Indium Oxide Obtained by the Sol−Gel Method and Their Gas-Sensing Properties

Abstract: Aging-induced aggregation of the nanoparticles in the colloidal solution of indium hydroxide leads to the formation of micrometer particles in the form of well-shaped blocks. As shown by high-resolution transmission electron microscopy and selected area electron diffraction, the well-shaped blocks have a polycrystalline nature composed of small nanounits. After calcination at 400 °C, they consist of cubic and hexagonal In 2 O 3 . Semiconducting sensors, composed of well-shaped blocks of cubic and hexagonal In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(65 citation statements)
references
References 38 publications
0
62
0
Order By: Relevance
“…On the other hand, far fewer studies have made on n-type oxidefunctionalized n-type oxide semiconductor sensors compared to p-type oxide-functionalized n-type oxide semiconductor sensors despite their remarkable sensing properties. In 2 O 3 is an n-type wide direct bandgap semiconductor (E g ¼ 3.55e3.75 eV) [14]. In 2 O 3 showed excellent response to several gases such as O 3 , NO 2 , CO and H 2 [15e19].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, far fewer studies have made on n-type oxidefunctionalized n-type oxide semiconductor sensors compared to p-type oxide-functionalized n-type oxide semiconductor sensors despite their remarkable sensing properties. In 2 O 3 is an n-type wide direct bandgap semiconductor (E g ¼ 3.55e3.75 eV) [14]. In 2 O 3 showed excellent response to several gases such as O 3 , NO 2 , CO and H 2 [15e19].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the synthesis of nanostructured In 2 O 3 compounds have attracted special attention in fundamental study, such as nanorods [1], nanowires [18,19], nanofibers [20,21], nanotubes [22,23], nanobelts [24,25], nanocubes [26][27][28], and nanoparticles [29][30][31]. Meanwhile, it is necessary to synthesize ordered threedimensional (3D) structured In 2 O 3 nanocomposite/microcomposite for the development of a nanodevice/microdevice with high performance in gas-sensing.…”
Section: Introductionmentioning
confidence: 99%
“…No impure phases corresponding to titanium compounds were detected. Gurlo et al [13] reported that the cubic to hexagonal phase transition was supposed to be favored under ambient conditions when foreign atoms (Fe 3+ , Sn 4+ ) with a smaller ionic radius than indium were substitutionally introduced into the cubic indium oxide network. However, this type of phase transformation was not observed for the Ti 4+ -doping into the In 2 O 3 lattice.…”
Section: Analysis and Measurementmentioning
confidence: 99%